Fountain of youth for squamous cell carcinomas? On the epigenetic age of non‐small cell lung cancer and corresponding tumor‐free lung tissues. Issue 12 (16th October 2018) - Marwitz, Sebastian; Heinbockel, Lena; Scheufele, Swetlana; Kugler, Christian; Reck, Martin; Rabe, Klaus F.; Perner, Sven; Goldmann, Torsten; Ammerpohl, Ole
Abstract : Aging affects the core processes of almost every organism, and the functional decline at the cellular and tissue levels influences disease development. Recently, it was shown that the methylation of certain CpG dinucleotides correlates with chronological age and that this epigenetic clock can be applied to study aging‐related effects. We investigated these molecular age loci in non‐small cell lung cancer (NSCLC) tissues from patients with adenocarcinomas (AC) and squamous cell carcinomas (SQC) as well as in matched tumor‐free lung tissue. In both NSCLC subtypes, the calculated epigenetic age did not correlate with the chronological age. In particular, SQC exhibited rejuvenation compared to the corresponding normal lung tissue as well as with the chronological age of the donor. Moreover, the younger epigenetic pattern was associated with a trend toward stem cell‐like gene expression patterns. These findings show deep phenotypic differences between the tumor entities AC and SQC, which might be useful for novel therapeutic and diagnostic approaches. Abstract : What's new? Chronological age is correlated with the methylation status of CpG sites in the genome, enabling the study of aging‐related phenomena. Here, investigation of molecular age loci in cells from patients with non‐small cell lung cancer (NSCLC) reveals remarkable differences in NSCLC cell epigenetic age compared to the host's chronological age. Adenocarcinomas showed a higher epigenetic age than squamous cell carcinomas (SQC). Reduced SQC epigenetic age was accompanied by increased expression of stem cell gene signatures, suggesting an increased abundance of stem cells in SQC. Elevated stem cell levels could have clinical implications, as stems cells often show therapeutic resistance.